Od Preglja do Gruma - Kralj, Lado (Slavistična revija, 1999)
The paper deals with expressionist drama with respect to the existing major works of research - which have largely covered the major issues - on Slovene literary expressionism and provides criteria for the selection of those dramatic works that exhibit clear features of expressionism. Such a selection makes sense because the fundamental substratum of this period still frequently compiles with symbolist poetics, despite the fact that it was already on the wane.
Keywords: ekspresionizem; Expressionism; Slovene literature; slovenska dramatika; slovenska književnost